Concomitant expression of far upstream element (FUSE) binding protein (FBP) interacting repressor (FIR) and its splice variants induce migration and invasion of non‐small cell lung cancer (NSCLC) cells. Issue 3 (8th September 2015) - Müller, Benedikt; Bovet, Michael; Yin, Yi; Stichel, Damian; Malz, Mona; González‐Vallinas, Margarita; Middleton, Alistair; Ehemann, Volker; Schmitt, Jennifer; Muley, Thomas; Meister, Michael; Herpel, Esther; et al.
Abstract: Transcription factors integrate a variety of oncogenic input information, facilitate tumour growth and cell dissemination, and therefore represent promising therapeutic target structures. Because over‐expression of DNA‐interacting far upstream element binding protein (FBP) supports non‐small cell lung cancer (NSCLC) migration, we asked whether its repressor, FBP‐interacting repressor (FIR) is functionally inactivated and how FIR might affect NSCLC cell biology. Different FIR splice variants were highly expressed in the majority of NSCLCs, with the highest levels in tumours carrying genomic gains of chromosome 8q24.3, which contained the FIR gene locus. Nuclear FIR expression was significantly enriched at the invasion front of primary NSCLCs, but this did not correlate with tumour cell proliferation. FIR accumulation was associated with worse patient survival and tumour recurrence; in addition, FIR over‐expression significantly correlated with lymph node metastasis in squamous cell carcinomas (SCCs). In vitro, we applied newly developed methods and modelling approaches for the quantitative and time‐resolved description of the pro‐migratory and pro‐invasive capacities of SCC cells. siRNA‐mediated silencing of all FIR variants significantly reduced the speed and directional movement of tumour cells in all phases of migration. Furthermore, sprouting efficiency and single cell invasiveness were diminished following FIR inhibition. Interestingly, the silencing of FIR isoforms lacking exon 2 (FIR Δexon2 ) alone was sufficient to reduce lateral migration and invasion. In summary, by using scale‐spanning data derived from primary human tissues, quantitative cellular analyses and mathematical modelling, we have demonstrated that concomitant over‐expression of FIR and its splice variants drives NSCLC migration and dissemination. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.